MENGGAGAS PENDIDIKAN BERWAWASAN KEWIRAUSAHAAN DI PERGURUAN TINGGI ISLAM - Hidayah, Nur (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2017)
There has been a concern over a high unemployment rate among graduates of Islamic higher education and a low proportion of entrepreneurs in Indonesia. In fact, a high proportion of entrepreneurs is one of indicators of a country’s welfare. This has generated a question: to what extent do Islamic values cultivate entrepreneurial culture among its adherents? How to cultivate entrepreneurial culture in Islamic higher education? This paper will investigate this matter using a case study of Faculty of Islamic Law and Economics at Banten State Institute for Islamic Studies.  The paper argues that the curriculum at the faculty of Islamic Law and Economics has not been oriented towards building entrepreneurial culture. The curriculum consists of subjects to enhance the students’ competence and skills to prepare them as bachelors of syari`ah economics for the professions such as manager, lecturer, researcher, syari`ah auditor, etc, instead of preparing them for entrepreneurs who are capable to build his or her own business from the scratch.    To propose Islamic entrepreneurship study program at the FSEI of IAIN SMHB, it is important to have a strong political will not only from the internal IAIN but also higher authoritative body such as the Ministry of Religious Affairs to facilitate this from not only the accreditation process but also financial support. A further feasibility study needs to be undertaken to build its infrastructure such as qualified lecturers, appropriate curriculum structure, and recruitment student system. Since this field has a strong link with a ‘real sector’, there has been an urgent need to build cooperations with business sector to enable the students to undertake their apprentice and build their networks to facilitate their ability to develop their own business.     Keywords: Islam, entrepreneurship, entrepreneurial education.